Police use of force under international law - Casey-Maslen, Stuart (Cambridge University Press, 2017)
A history of law enforcement -- Policing and social and economic policy -- Core principles governing use of force for law enforcement -- Use of firearms -- Use of "less-lethal" weapons -- Facilitating peaceful protest and ensuring crowd safety during assemblies -- Use of force in custodial settings -- Use of force in counterterrorism -- Private security and use of force -- Counterpiracy at sea -- Accountability